Medical Research Trends in Undergraduate Psychological Theses: A report from a South American country - Carbajal-León, Carlos (2023)
Introduction: Psychological research can be developed by researchers and also by undergraduate or postgraduate students. In an undergraduate level, psychological research is specially challenging due to the limited ability of students to develop coherent and logical research problems and methodological approaches. Objective: The objective of this study is to identify the main research trends in undergraduate psychological theses from Peruvian universities. As a specific objective, quantitative and qualitative research design trends were distinguished. Methods: A descriptive and retrospective systematic review of psychological research thesis of Peruvian undergraduate students was conducted, starting the data extraction process starting with RENATI database for an initial screening phase. Data analysis was conducted in two phases. Results: First, data was organized in relation to its frequency of the categories of authors' sex, the universities were catalogued as universities 1, 2, 3, 4 and 5 according to their ranking, the categories of years of publication, number of authors, designs, type of methodology, and area of publication were obtained. Descriptive frequency statistics were established based on these categories. In the next phase, lexicometric and statistical textual analysis were used to identify research trending topics. Discussion: The main results show that different topics are predominantly framed within the clinical and health psychology line of research, mainly those related to coping styles, psychological stress and wellbeing. © 2023, Faculty of Medical Sciences, Santa Rosa del Aguaray Branch, National University of Asuncion